Characteristics and experiences of targeted parents of parental alienation from their own perspective: A systematic literature review. (19th September 2018) - Lee‐Maturana, Saulyn; Matthewson, Mandy; Dwan, Corinna; Norris, Kimberley
Abstract : Objective: The aims of this systematic literature review were to identify and synthesise all relevant information about targeted parents' characteristics and experiences from their own perspective. Method: The academic databases Web of Science, PsycINFO, PubMed, EMBASE‐ELSEVIER, The Cochrane Central Register of Controlled Trials, and conference abstracts were systematically searched from their inception until May 2018. The systematic review followed the preferred reporting items for systematic reviews and meta‐analyses protocol (PRISMA‐P) and was registered in PROSPERO (ID = CRD42017062533). Results: Nine relevant articles were included after conducting inclusion criteria and quality assessment. Data were collated and analysed using guidance on the conduct of narrative synthesis in systematic reviews. Conclusion: Targeted parents report consistent stories about the nature of the alienation tactics used by alienating parents across the included studies. Targeted parents expressed dissatisfaction with legal and mental health system services available to them. Further, despite feeling despair, frustration, and isolation, targeted parents appear to be resilient and seek out positive coping strategies. This review showed that research on targeted parents from their own perspective is sparse, and more studies are needed.